Delays in new product introduction: Experiences of a food processing company in a developing economy. Issue 5 (13th August 2018) - Adaku, Ebenezer; Amoatey, Charles Teye; Nornyibey, Israel; Famiyeh, Samuel; Asante-Darko, Disraeli
Abstract : Purpose: Speed to the market is becoming a key competitive priority in developing countries' environments even though lack of technology, poor skilled labour and under-developed infrastructure remain daunting challenges. The purpose of this paper is to examine the causes and relative importance of delay factors in the introduction of food products to the market in the era of time-based competition. Design/methodology/approach: The study employed a case study approach in understanding the phenomenon in its natural settings and making sense of it through process and participants observations. Again, a two-stage approach (first, interviews and second, questionnaire) was used in collecting data from the respondents who work in a project team for a large food processing firm. The data was analysed using the relative importance index technique. Findings: The results show that the most important causes of delays in new products introduction, especially in the food processing industry, are: high number of projects running concurrently; lack of project management process; lack of consistent project management structure; high workload on project team and delays caused by external laboratory. Originality/value: This study sought to identify detailed delay factors in the introduction of new products with respect to the food processing industry and more importantly established the relative importance of these delay factors as a decision support system for managers in the food processing industry.